THE SOCIAL DIMENSIONS OF MUSIC EDUCATION - BÍRÓ, István Ferenc; HÖRICH, Balázs; SZALAI, Tamás; VÁRADI, Judit (Studia Universitatis Babes-Bolyai Musica, 2020)
The aim of our study is to explore the factors influencing the cultural sensitivity of students aged 8–13 years. We set up our hypotheses based on the theory of Bourdieu and Passeron and the research of Hunyadi. Our main question is instrumental studies, the frequency of singing, and social status how affect cultural consumption. In our research, we examined the impact of parents’ attitudes to music on children’s musical consumption. To examine the role of cultural capital, we used international models. The aim of our exploratory research is to examine in what form and to what extent the different manifestations of cultural capital prevail in the dimension of cultural consumption. Our results supported that higher education, higher parental care, parents’ musical capital, and good financial status increase the chances of cultural consumption. Those family with higher social status can be characterized by a broader cultural consumption pattern, which in turn is accompanied by more frequent musical activity. Families in a better position are characterized not only by higher cultural consumption but also by more prudent methods of cultural transmission.